MATH SOLVE

2 months ago

Q:
# which expression is a factor of 10 x 2 + 11 x + 3

Accepted Solution

A:

Answer: the two factors are (5x + 3) and (2x + 1)

Explanation:

I will find the two factors of 10x² + 11x + 3.

You can use either the quadratic formula of factor.

I will use the quadratic formula:

1)

[tex]x= \frac{b^2 +/- \sqrt{b^2-4ac} }{2a} [/tex]

[tex]x= \frac{-11+/- \sqrt{11^2-4(10)(3)} }{(2)(10)} [/tex]

x = -3/5 and x = -1/2

2) the factors are: x - (-3/5) = 0 and x - (-1/2) = 0

Simplify them.

3) x - (-3/5) = 0

5x + 3 = 0

4) x - (-1/2) = 0

2x + 1 = 0

5) Then the two factors are: (5x + 3) and (2x + 1).

6) verify:

(5x + 3)(2x + 1) = 10x² + 5x + 6x + 3 = 10x² + 11x + 3 which is the original expression.

Explanation:

I will find the two factors of 10x² + 11x + 3.

You can use either the quadratic formula of factor.

I will use the quadratic formula:

1)

[tex]x= \frac{b^2 +/- \sqrt{b^2-4ac} }{2a} [/tex]

[tex]x= \frac{-11+/- \sqrt{11^2-4(10)(3)} }{(2)(10)} [/tex]

x = -3/5 and x = -1/2

2) the factors are: x - (-3/5) = 0 and x - (-1/2) = 0

Simplify them.

3) x - (-3/5) = 0

5x + 3 = 0

4) x - (-1/2) = 0

2x + 1 = 0

5) Then the two factors are: (5x + 3) and (2x + 1).

6) verify:

(5x + 3)(2x + 1) = 10x² + 5x + 6x + 3 = 10x² + 11x + 3 which is the original expression.